Power lines : giant hydroelectric power in the Pacific Northwest, an era and a career - McCormmach, Russell (Palimpsest Books, 2023)
"The Columbia River and its tributaries hold the greatest hydroelectric power potential of any river system in America. The systematic development of the potential began with a survey of the Columbia River Basin by the US Army Corps of Engineers. Its subsequent report to Congress in 1931 recommended construction of a system of multipurpose dams of unprecedented size, difficulty, and expense. During the Great Depression, as part of President Roosevelt's efforts to remove men from relief roles, the federal government undertook to build two dams on the Columbia River following the Corp's master plan. They were completed in time to aid to the production of weaponry in World War II. Through the postwar economic boom, the government built more dams, distributing giant blocks of power to industry in a region whose economy until then had been mainly extractive. With a focus on the Pacific Northwest, this book treats of federal power in the dam-building era in America. The legacy of that era is conflicted. The hydroelectric development of the Columbia River Basin is incontrovertibly both one of the great technological achievements of the twentieth century and a massive incursion into nature. In keeping, this book discusses the development both from the side of engineering, the source of problems in the dam-building era, and from the side of nature, the source of problems in the era that succeeded it, the environmental. The Columbia River Basin is home to the country's greatest salmon runs, and dams have threatened their survival, even as nowhere else has so much effort and expense been directed to preserving them. Problems of power and of the environment have an urgency in today's world, and measures that address them are often contradictory. This book considers the measures and the place of hydroelectricity among alternative sources of energy."--from publisher